Modern Approches in the Study of Tick-Borne Infections Fod Based on Modular Methods - N. V. Rudakov; S. A. Rudakova; A. P. Efimova; O. M. Drozdova; A. F. Lubenko; Yu. A. Petrova; V. V. Yakimenko; V. A. Dedkov (Эпидемиология и вакцинопрофилактика, 2017)
This paper presents a new ecological and epidemiological data on the distribution and the epidemic manifestation of natural foci of tick-borne infections in the Kemerovo region, taking into account the study of their combination with the use of modern molecular biology methods.